The feasibility of the land readjustment technique as a tool to improve urban development and land supply in Dhaka, Bangladesh - Mowla, Quazi Sirajul; Archer, Ray W.; Kammeier, Hans Detlef; Miah, M.A. Quader; Norwegian Agency for Development (NORAD) (Bangkok : Asian Institute of Technology, 1994)
The south-eastern fringe of Dhaka (i.e. the DND agricultural project zone) is protected from flood by embankment all around the area. Due to the scarcity of flood free areas at the fringe of Dhaka, the DND project zone is transforming very fast from rural to urban uses, but this is in an unplanned and haphazard way. In various studies and reports, the zone has been identified as having high potential for urban development in the next decade. It has also been urged by different consultants and experts to adopt new innovative techniques for urban land development and to test them in specified areas there. The Capital Development Authority (RAJUK) is trying to implement a 'land readjustment (LR)' demonstration project on a small area within the DND zone, which reflects the government's awareness of the problems there. The LR technique has the advantage of achieving the planned development of serviced lands with no or minimum cost to government, as the costs are recovered through the sale of a portion of the serviced land. It is successful in the countries that it is practiced in and highly praised through different publications, reports and seminars. Bangladesh has attempted to check the viability of the technique very recently but the model devised for land readjustment deviated quite significantly from the standardized international LR technique. The present study aims to see the viability of a LR scheme which follows every steps of a true LR scheme. The study also aimed to find out the limitations on LR in Dhaka and to examine the prospects and the possible ways to overcome these. The study area selected is an area of 9.7 hectare of land, near to government's site for its 'LR' project. The study area is mostly vacant, and consisted of 117 separate land parcels which is natural for a flood free urban areas of Dhaka. In the proposed LR scheme, the landowners will have to give up 22.15 percent of their land for roads and other community facilities plus 11.46 percent of the serviced plots to be sold to recover the project cost. The landowners would be left with 66.39 percent of their original land as building plots. They will have an estimated net land value gain of about 88.5 percent after cost recovery, which should make the scheme readily acceptable and help to bring this area into for efficient urban use through the market. The draft LR scheme seems to be technically and financially feasible. Fifty four out of 98 (55.1 % ) landowners, expressed their inclination towards the first outline scheme and the rest ( 44.9%) were skeptical about the project. To overcome the skepticism, the study indicates alternate approaches within the existing limitations. To make the LR technique socially and politically more acceptable, some legislative and institutional reform might be required to make the project successful. However, sincere willingness from beneficiary groups for the planned urban development might override all the apparent hindrances.
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Science
Thesis (M.Sc.) - Asian Institute of Technology, 1994
Keywords: City planning -- Bangladesh -- Dhaka